2015
DOI: 10.3109/10641955.2015.1077859
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thiol/Disulphide Homeostasis in Preeclampsia

Abstract: Serum thiol/disulphide homeostasis may have a role in the pathogenesis and can be evaluated with the clinical and laboratory findings of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…It has been demonstrated that TDH was shifted in favor of oxidative status in preeclampsia, pregnant women diagnosed with idiopathic recurrent pregnancy loss, pregnant women diagnosed with Familial Mediterranean fever, pregnant women with fetal neural tube defects and vaginitis patients [89][90][91][92][93].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
“…It has been demonstrated that TDH was shifted in favor of oxidative status in preeclampsia, pregnant women diagnosed with idiopathic recurrent pregnancy loss, pregnant women diagnosed with Familial Mediterranean fever, pregnant women with fetal neural tube defects and vaginitis patients [89][90][91][92][93].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
“…Demonstrating the destructive effects of oxidative stress can elicit valuable information in terms of understanding the biochemical process involved in many diseases [14][15][16]. The TDH measurement method newly developed by Erel et al [8,15,[17][18][19][20][21][22] has been shown to a reliable indicator in showing oxidative stress.…”
Section: The European Research Journal Volume 5 Issue 2 March 2019mentioning
confidence: 99%
“…[25] Serum total thiols as a marker of oxidative stress, have been studied in various systemic diseases like ischaemic heart disease, diabetes, pulmonary diseases, Alzheimer's disease, preeclampsia, kidney diseases and alcoholism. [26,27,28,29,30,31,32,33] Serum thiols have also been studied in ophthalmic diseases like keratoconus, pseudo exfoliation syndrome and cataract. [34,35,36] As regards thiol levels in CSCR, thorough review of scientific periodicals yielded only two studies in Turkish population, that assessed total thiol in CSCR, of which only one was done in acute CSCR.…”
Section: Discussionmentioning
confidence: 99%